1981
DOI: 10.1051/rnd:19810110
|View full text |Cite
|
Sign up to set email alerts
|

The reproductive cycle in the male hedgehog (Erinaceus europaeus L.) : a study of endocrine and exocrine testicular functions

Abstract: Summary. Seasonal Introduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…It has been established that the onset of spermatogenic activity occurs during the denning period in black bears [5,24] and brown bears [25] as well as in other deep hibernating mammals such as ground squirrels [10,12], European hedgehogs [4,21], and golden hamsters [22]. Serum testosterone profiles of black bears indicated that the activity of the reproductive endocrine system begins to increase during denning [11,17,24].…”
mentioning
confidence: 99%
“…It has been established that the onset of spermatogenic activity occurs during the denning period in black bears [5,24] and brown bears [25] as well as in other deep hibernating mammals such as ground squirrels [10,12], European hedgehogs [4,21], and golden hamsters [22]. Serum testosterone profiles of black bears indicated that the activity of the reproductive endocrine system begins to increase during denning [11,17,24].…”
mentioning
confidence: 99%
“…Plasma testosterone at 57°N shows a period of elevation 2 months shorter in duration than at 46°N (Saboureau & Boissin, 1978;Saboureau & Dutourné, 1981), rising and falling 1 month later and earlier respectively. This later reactivation, and earlier involution, is associated with the shorter summers at 57°N, spermatogenesis occurring over a shorter period.…”
Section: Discussionmentioning
confidence: 99%
“…Testicular activity, including an increase in testis size and rising testosterone levels, has been reported to start towards the end of heterothermy in some hibernators, eg Belding's ground squirrels Spermophilus beldingi (Bushberg and Holmes 1985), Golden-mantled ground squirrels S. lateralis (Barnes et al 1988), Uinta ground squirrels S. armatus (Ellis et al 1983), woodchucks Marmota monax (Concannon et al 1989), Turkish hamsters Mesocricetus brandti (Darrow et al 1987), and European hedgehogs Erinaceus europaeus (Saboureau and Dutourné 1981).…”
mentioning
confidence: 99%